(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The focus of the present research paper is to show changing thinking and perspective of Indian towards British rule and their policies. The novel clearly presents intention of policies of British Empire to control and rule Indian continent politically, economically and socially. In the beginning of expansion of British rule, Indian people believe that British rule would improve poor condition of Indian people with the help of various political and economic policies. But with passage of the time, they get realized that British people are not here to develop the Indian continent but to satisfy their vested interests.